2022
DOI: 10.1039/d2ob00536k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of pentasubstituted pyrroles via intramolecular C-arylation

Abstract: Immobilized L-aspartic acid beta-methyl ester (Fmoc-Asp(OMe)-OH) was reacted with 4-nitrobenzensulfonyl chloride followed by alkylation with various -haloketones. The resulting intermediates were treated with potassium trimethylsilanolate, which yielded tetrasubstituted pyrroles after...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Interestingly, only utilizing TMSOK led to the formation of product 6a , whereas all other tested bases furnished either the starting material or mixtures of unknown compounds. This result proves that the base-specificity is very large and even higher than that of pyrrol cyclization, for which lithium diisopropylamide (LDA), tert -butylimino-tri­(pyrrolidino)­phosphorane (BTTP), and sodium hydride were also applicable . Additional experiments revealed that even 0.03 M TMSOK triggered the conversion (although incomplete), whereas lowering the concentration to 0.003 M was not applicable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, only utilizing TMSOK led to the formation of product 6a , whereas all other tested bases furnished either the starting material or mixtures of unknown compounds. This result proves that the base-specificity is very large and even higher than that of pyrrol cyclization, for which lithium diisopropylamide (LDA), tert -butylimino-tri­(pyrrolidino)­phosphorane (BTTP), and sodium hydride were also applicable . Additional experiments revealed that even 0.03 M TMSOK triggered the conversion (although incomplete), whereas lowering the concentration to 0.003 M was not applicable.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfonamide 3 was alkylated with 2-bromo-1-(p-tolyl)ethan-1-one, and the resulting resin 4 was treated with 0. as previously reported for the synthesis of pyrroles. 21 The similar course of the reaction was observed, and after being cleaved from the polymer support with trifluoroacetic acid (TFA), the pyridine product 6a was obtained in good crude purity (above 50%, calculated from UHPLC-UV traces) and overall yield (39%, calculated after the final purification from the loading of Rink amide resin).…”
Section: ■ Introductionmentioning
confidence: 99%
“…To convert intermediate 3 a to desired product 4 a , potassium trimethylsilanolate (TMSOK) was initially applied as recently reported for preparing pyrroles [6] . The reaction yielded a separable mixture of two products in a ratio of 3 : 2, with the major product being 2‐(4‐nitrophenyl)‐3‐phenylquinoline‐4‐carbonitrile 4 a .…”
Section: Resultsmentioning
confidence: 99%
“…Different 5‐ and 6‐membered nitrogen heterocycles were proven to be accessible by this synthetic approach (Figure 1). [5,6] In contrast, the application of Truce–Smiles rearrangement to N ‐aryl nitrobenzenesulfon‐amides has not been reported. Inspired by this fact, we suggested 2‐aminobenzyl cyanide as the starting amine for preparing N ‐(2‐(cyanomethyl)phenyl)‐4‐nitrobenzene‐sulfonamides, which are eventually applicable to synthesizing 4‐functionalized‐2,3‐diarylquinolines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation